Investigation of the Relationship Between Soil Erosion, Land Cover and Hemeroby Level in Cserépfalu by Analysing Soil Profiles - Dobos, Anna; Hegyi, Tamás Péter; Zelei, Zoltán; Hegyi, Balázs (Journal of Environmental Geography, 2023)
We can measure the effects of anthropogenic processes to the nature in case of hilly agricultural areas with the rate of soil (water) erosion. There is actual question what kind of connection could be shown between the rate of soil erosion, land cover categories and hemeroby levels? How can the intensity of antropogenic effects influence the rate of soil erosion? We did some research work in the North Hungarian Region, in Cserépfalu in 2014. In Cserépfalu, the northern areas are under nature conservation and belong to the Southern Bükk Mountains while the southern dissected pediment is the extensive agricultural territory. We described the soil types in the southern areas using the soil description method of FAO. We collected data about the rate of soil erosion, the land cover types, slope angle, slope forms, slope aspect and data for the relief conditions too. We could point out the sheet erosion around the 15 investigated soil profiles and we could found 3 strongly eroded, 8 medium eroded and 4 accumulated soil profiles. The land cover categories were given based on FAO category system and topographic map from 1990. Our results showed that land cover categories were changed in time and it caused the change of hemeroby levels as well. The intensity of land cultivation in investigated areas was changed. We could point out in some cases that the stronger soil erosion rate was caused by former land cover system. In summary, some former agricultural areas were changed and became as an abandoned areas so that the antropogenic effects were decreased in extensive agricultural areas in Cserépfalu. Our results can be compared with another pediments dissected by valleys where extensive agricultural areas are characteristic in Hungary.